DOUBLE ENTRY BOOKKEEPING DALAM AKUNTANSI - Ulfah, Almira Keumala (J-ISCAN: Journal of Islamic Accounting Research., 2019)
Accounting has an important role in the business world where accounting provides financial information that can be used by economic entities to stakeholders (both internal and external parties. Each economic entity must present its financial information to all stakeholders. To facilitate economic entities in making records in financial transactions, and to make it easier for stakeholders to understand financial information conveyed by economic entities, there must be uniformity in accounting.The Golden Rule of Accounting brings uniformity and to be able to present transactions correctly.The important rules contained in the Golden Rule of Accounting form the basic equation accounting and accounting in pairs (double entry). Keywords: Double entry, Accounting Abstrak Akuntansi memiliki peran penting didalam dunia bisnis di mana akuntansi memberikan informasi keuangan yang dapat digunakan oleh entitas ekonomi kepada para pemangku kepentingan (baik pihak internal maupun pihak eksternal). Setiap entitas ekonomi harus menyajikan informasi keuangannya kepada semua pemangku kepentingannya. Untuk memudahkan entitas ekonomi dalam melakukan pencatatan dalam transaksi keuangannya, serta untuk memudahkan pemangku kepentingan untuk memahami informasi keuangan yang disampaikan oleh entitas ekonomi maka harus ada keseragaman dalam akuntansi. Golden Rule Of Accounting membawa keseragaman dan untuk dapat menyajikan transaksi dengan benar. Aturan penting yang terdapat di dalam Golden Rule Of Accounting membentuk persamaan dasar akuntansi dan pembukuan akuntansi secara berpasangan (double entry). Kata kunci: Double entry, Akuntansi.